Atlas Linguístico dos Falares de Manaus – ALFAMA - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
To map out the speeches of geographical spots previously delimited is the purpose of the linguistics atlas. This paper, entitled Linguistics Atlas of Speeches from Manaus - LASM - introduces itself in the initiative of presenting, with the application of a phonetic-phonological questionnaire, the speeches of a region, Manaus for this matter, a city which had not been investigated by the Amazon Linguistics Atlas – ALA. Thus, the LASM, composed of two volumes, with the assessment of Dialectology and the sociolinguistic approach, has selected four representative districts from the capital of Amazonas, which are: Alvorada (Middle West Area), São Raimundo (West Area), Educandos (South Area) and Colônia Antônio Aleixo (East Area), choosing six informers on each of them, men and women, disposed each one on three age groups (18 to 35 years old, 36 to 55 years old and 56 upward), with low educational level, that is, were illiterate or had an educational level up to the 8th grade on elementary school. Furthermore, it sought to apply the questionnaire to 24 informers who were manauaras or those who had moved to the city early on, considering that Manaus, as capital and main economical center of North Region, is composed of many migratories flows. From these standards, 159 questions were made with the purpose of collecting phonetical phenomenon, connected to the aspects of vocalism and consonantism within the brazilian portuguese. The answers were inserted on the linguistics letter generating software SGVCLin (Software para Geração e Visualização de Cartas Linguísticas), designed by Seabra, Romano e Oliveira (2015), composing the second volume of this atlas. Among the results, it was made notable the closed execution of the anterior and posterior pretonical middle vowels, the diphthong management [ey] and the diphthong fading [ow]; the -R post-vocal with predominance to the deaf glottical fricative and -S in syllabical coda with predominanceto to the post-alveolar fricatives. Thus, with the making of this atlas, its purpose is to contribute to the knowledge of linguistic reality of the North Region and to incite the production of other dialectological researches on the amazonian capital.
Atlas of Speeches from Manaus – LASM
Keywords: Dialetologia; Atlas; Fonética/Fonologia - Manaus; LINGUÍSTICA, LETRAS E ARTES: LINGUÍSTICA: SOCIOLINGUÍSTICA E DIALETOLOGIA